Phylogenetic and Morphological Analysis of Bostrychus sinensis (Gobiiformes: Eleotridae) from Musi River, South Sumatra - Sofian Sofian; Selviani Selviani; Indah Anggraini Yusanti; Humairani Humairani; Sujaka Nugraha; Leni Maryani; Rahma Mulyani; Ahmad Sundoko; Nadia Jely Monica; Haspen Wijaya; Iwan Kuncoro; Fazril Saputra (Universitas Gadjah Mada, 2026)
Bostrychus cf. sinensis, a member of the family Eleotridae, was first identified in the Muara Telang region, Banyuasin, South Sumatra. Specimens collected from tidal channels were subsequently analyzed genetically using DNA barcoding with the Cytochrome Oxidase Subunit 1 (COI) gene. The molecular analysis revealed that the Muara Telang specimens shared 98.55% genetic similarity with Bostrychus sinensis from the Seom River, South Korea. According to genetic guidelines, a divergence greater than 3% may indicate a distinct species. The genetic divergence observed was 0.243, equivalent to 243 nucleotide variations out of 1,000 bases analyzed. Phylogenetic analysis showed that Bostrychus cf. sinensis from Muara Telang clustered within the same clade as Bostrychus sinensis but still exhibited genetic polymorphism at 8 distinct sites. Therefore, this specimen was designated as Bostrychus cf. sinensis. The COI gene sequence data for Bostrychus cf. sinensis from Muara Telang have been deposited in GenBank under accession MK777294.1.